Study of association of thyroid disorders with abnormal uterine bleeding - Ghosh, Runoo; Patel, Rakesh R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Abnormal uterine bleeding from the vagina that is usually occurred when ovary do not release egg and if it occurred during fertile period leads to various complication like anemia, Infertility etc. and among all causes one of the most common cause of abnormal uterine bleeding is disturbance in level of Thyroid hormones. Methods: 100 female Patients of age group between 20-45 having complain of Abnormal uterine bleeding visited at Gynec OPD of our institute were included in this study. fasting blood samples was taken from all participants and samples were analyzed for Thyroid function test (TSH, T3, T4) at central laboratory of our hospital. Obtained data was analyzed statistically by using prizam software. Results: The bleeding abnormality that is found most of the women is polymenorrhaggia and menorrhaggia. 32% of patients who were studied had thyroid dysfunction, of which 18% of patients had subclinical hypothyroidism, 11% of patients had hypothyroidism and only 3% of patients had hyperthyroidism. Conclusions: Present study concludes that thyroid dysfunction should be considered as an important etiological factor for menstrual abnormality especially during fertile period.